EFFECTS OF INK CONSUMPTION ON PRINT QUALITY ON COATED CELLULOSE-BASED PAPER SURFACES - (:unkn) unknown (EDITURA ACAD ROMANE, 2020)
Paper - ink interaction is extremely important in printing. Ideal printing outputs should be achieved with minimal ink consumption. It should not be supposed that visual printing quality will increase as the amount of ink increases. The effects of excessive ink consumption during the printing process on process sustainability, economy and environment should not be ignored. In this study, the effects of ink consumption during the printing process on printing quality parameters were mainly examined. Paper samples were printed with different amounts of ink, and the density and CIE L*a*b* values of the solid ink films were measured. The lightfastness test was applied to determine the resistance of the printed ink films to light, and the changes in their color were examined. Ideal ink amounts to reach ideal color L*a*b* values were determined and the effects of ink amount on the printing quality parameters were highlighted. Then, ink consumption was evaluated in terms of recycling, sustainability, environmental and economic effects, and recommendations were made to reduce the use of ink.
Keywords: ink amount; ink consumption; print quality; environmental; CIE L*a*b*; color change